Do naturalismo moral à semiótica dos valores na filosofia de Nietzsche - Onofri, Wilson Luciano (2018)
The present work aims at presenting a critique of the propositional scope of the naturalistic character of Nietzsche 's thinking about moral naturalism and then shows how this propositional aspect of the philosopher' s mature thought can be better understood in the context of a semiology of values . In this sense, we reconstruct the main lines of the naturalist itinerary, whose main purpose is the reversion of Platonism, and then we make acritical analysis of the most diverse approaches within the scope of this exegetical line and its respective topics, among which we can highlight the problem of substantive naturalism, methodological naturalism, the naturalistic fallacy, among others. In the end we will show how the philosopher's critical program of putting the current values in question is instrumentalized in his task of "constructing" new values immanently.